RANCANG BANGUN SISTEM INFORMASI PENJUALAN KAP LAMPU BERBASIS WEB PADA JAYA LAMP - Andyka Pratama Putra; Nardiono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Jaya Lamp is a line of business engaged in the manufacture and sale of lampshades. In marketing and selling lampshades, Jaya Lamp still uses a simple system such as social media which raises several obstacles, namely the small scope of product marketing and less known by the public. To optimize Jaya Lamp's marketing, in writing this thesis a sales information system website was created to display product information that has been produced by Jaya Lamp. So that customers can become members and can easily place orders and purchase lampshades online. The purpose of this research is to build a web-based product sales information system as a promotional medium to expand the sales area and can be accessed by consumers which includes various kinds of products, sales transactions and making sales reports. With this web-based sales system, marketing transactions and business processes will become easier. This website was built using the Waterfall method as a system development method. The programming languages ​​used are HTML, PHP, MYSQLI database as storage and software testing is done by Blackbox Testing methods. With a web-based sales information system, sales and ordering transactions can be done more easily and consumers don't have to come directly to the Jaya Lamp Lampshade manufacturer.